Follow-Up and Validation of K2 and TESS Planetary Systems With Keck NIRC2 Adaptive Optics Imaging - Schlieder, Joshua E.; Gonzales, Erica J.; Ciardi, David R.; Patel, Rahul I.; Crossfield, Ian J. M.; Crepp, Justin R.; Dressing, Courtney D.; Barclay, Thomas; Howard, Andrew W. (Frontiers in Astronomy and Space Sciences, 2021)
High resolution imaging (HRI) is a critical part of the transiting exoplanet follow-up and validation process. HRI allows previously unresolved stellar companions and background blends to be resolved, vetting false positive signals and improving the radii measurements oftrue planets. Through a multi-semester Keck NIRC2 adaptive optics imaging program, we have pursued HRI of K2 and TESS candidate planet host systems to provide the transiting exoplanet community with necessary data for system validation and characterization. Here we present a summary of our ongoing program that includes an up to date list of targets observed, a description of the observations and data reduction, and a discussion of planetary systems validated by the community using these data. This observing program has been key in NASA's K2 and TESS missions reaching their goals of identifying new exoplanets ideal for continued follow-up observations to measure their masses and investigate their atmospheres. All observations presented here are available as calibrated images and resulting contrast curves through the Exoplanet Follow-up Observing Program (ExoFOP) website. We encourage members of the exoplanet community to use these data products in their ongoing planetary system validation and characterization efforts.